Building inclusive democracies in ASEAN - Mendoza, Ronald U.; Beja, Edsel L.; Teehankee, Julio C.; La Vina, Antonio G.M; Villamejor-Mendoza, Maria Fe (World Scientific Publishing Co.Pte.Ltd., 2019)
Containing the latest research and insights of academics and development practitioners pursuing political and economic reforms in the ASEAN region, Building Inclusive Democracies in ASEAN recognizes that a well-functioning democracy is part of what ultimately fosters inclusive growth and development. Inequitable access to democratic processes and mechanisms produce government policies and initiatives that are inconsistent with the needs of the majority. The chapters include empirical research on the symptoms and effects of traditional patron-client politics, experiences, insights, analyses, and policy recommendations, as well as reflections, on reform efforts along the lines of citizens' participation, transparency, and evidence-based policymaking